speaking Korean for beginners - Lee, Haiyoung; Kyo, Hwang In; Mee, Han Sang (Elizabeth, NJ Hollym International Corp, 2006)
This book has compiled so that readers can study spoken Korean on their own, acquiring both fluency and accuracy by listening to the accompanying CD, speaking korean for beginners, the most effective book for those just starting out with their study of the Korean language, incorporates useful expressions while providing key insights into Korean culture
13
Keywords: Korean Language; Korean Learning